“We cannot eat copper dust!”: An ethnographic study of the perceptions of copper mining in Concordia, South Africa - Maree, Shannah Ashleigh (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.